Investigating teachers’ perceptions and instructional practices regarding form- focused instruction of speech acts in the Iranian EFL context - Melahat Amir Jahansouz Shahi; Neda Gharagozloo; Reza Raissi (Universitas Pendidikan Indonesia, 2022)
Mastery over speech acts plays a significant role in the accomplishment of communication between interlocutors. Thus, the present study aimed to investigate Iranian EFL Instructors' perception and instructional practices towards form-focused instruction of speech acts, specifically request apology and invitation. To this aim, through a sequential explanatory mixed-methods design, the present researchers selected 30 English language instructors in Islamic Azad University (IAU) of North Tehran Branch based on criterion sampling as the study participants. All the participants completed an adapted version of Pragmatic Knowledge Questionnaire (PKQ), and were successively interviewed in terms of their claimed perceptions and practices regarding form-focused instruction of speech acts through a semi-structured interview. Finally, six classes were observed by the researchers to get informed of their real classroom practices. The results of data analyses were then triangulated, and the findings revealed that Iranian EFL instructors used explicit strategies rather than implicit strategies to instruct speech acts in their classes. Also, they presumed and agreed that explicit instruction is more effective since this technique seems to be easier, understandable and without ambiguity for the learners. The results of the current study are beneficial for EFL instructors, syllabus designers, materials developers, and scholastic administrators to enrich the current English language teaching curricula.